Դէպի Ս. Գրիգոր Նարեկացւոյ տաղից նոր հրատարակութիւն. Ասպարէզներ եւ նոր հեռանկարներ - Իւթիւճեան, Հայկ սրկ. («Նաիրի» հրատ.)
The present article is an introduction to the work carried out by the author on the textual, theological and musicological aspects of the neumes of St. Gregory of Narek. It commences with a history of editions, discusses the motivation behind a new critical edition, expounds the possible editorial approaches and procedures, and summarises the shortcomings of editions currently available. We argue that it would be inappropriate to impose a uniform editorial approach indiscriminately over the whole corpus, as the transmission of manuscript witnesses differs considerably from one ode to another, thus requiring a flexible, tailor-made approach in each case. Indeed, in one extreme instance the extant variants seem mutually irreconcilable. We also discuss misunderstood passages, and endeavour to clarify obscurities in the texts. We then turn to the neumatological conjectures made by Ełia Tntesean according to which metrical durations are associated with syllables bearing particular neumes or none; we demonstrate, by considering several examples, the extent to which layers of metre can thereby emerge. Finally, we seek to associate the metre emerging from such an approach with points of bifurcation of the phylogenetic tree, in the case of a particular example. Through the detailed analysis of concrete examples, the article hopes to offer a taste of some of the challenges and conundrums faced by the modern editor, as well as some novel perspectives. Настоящая статья является введением к работе автора над текстологическими, богословскими и музыковедческими аспектами од Григора Нарекаци. Она содержит историю изданий, обосновывает необходимость нового критического издания, поясняет возможные принципы и процедуры подготовки текста и подытоживает недостатки имеющихся изданий. Очевидно, одинаковый подход ко всему корпусу не приемлем, так как рукописные свидетельства разнятся от стихотворения к стихотворению, требуя в каждом отдельном случае гибкого, ювелирного подхода, причем имеется прмер, когда существующие варианты не возможно согласовать. Мы также пытаемся интерпретировать неправильно понятые и темные места. Затем обращаемся к невматологическим догадкам Е. Тнтесяна, согласно которым метрическая протяженность связана со слогами, несущими определенные невмы, либо лишенными таковых. Наконец мы пытаемся на одном конкретном примере связать метрику, выявленную благодаря невмам, с разветвлением генеалогического древа. Подробно анализируя конкретные примеры, надеемся создать представление о дилеммах и вызовах, стоящих перед современным издателем, а также о некоторых перспективах в этой области.
Keywords: Նոր հրատարակություններ; Գրիգոր Նարեկացի